Application of Pancasila Values in Character Building Efforts Elementary School Students in the Era of 21st Century - Komala Putri, Prillya; Dahnial, Irfan (Journal of Elementary School Education, 2023)
The purpose of this study is to describe the application of Pancasila values in an effort to build character in elementary school students which is very urgent in the 21st century era. In answering problems. This research method uses a qualitative approach through a descriptive method. The results showed that the importance of applying Pancasila values in an effort to build student character in the life of the nation and state, especially in responding to the challenges of the times that continue to develop. Pancasila as the basis of the state has the highest position in every aspect of life. Pancasila as a value system that is a single entity and cannot be separated. Therefore, the application of the values contained in Pancasila can become a moral force and support the formation of student character for the creation of a generation with Pancasila character and spirit.